Revision of the order Bothriocephalidea Kuchta, Scholz, Brabec & Bray, 2008 (Eucestoda) with amended generic diagnoses and keys to families and genera - Kuchta, Roman; Scholz, Tomás; Bray, Rodney A (Systematic parasitology, 2008)
The tapeworm order Bothriocephalidea Kuchta, Scholz, Brabec & Bray, 2008 (Platyhelminthes: Eucestoda), which has until recently formed part of the suppressed order Pseudophyllidea, is revised. Four new genera, namely Andycestus n. g. [type- and only species A. abyssmus (Thomas, 1953) n. comb.], Plicocestus n. g. [type- and only species P. janickii (Markowski, 1971) n. comb.] (both Bothriocephalidae), Mesoechinophallus n. g. [type-species M. hyperogliphe (Tkachev, 1979) n. comb.; other species M. major (Takao, 1986) n. comb. (Echinophallidae)] and Kimocestus n. g. [type- and only species K. ceratias (Tkachev, 1979) n. comb.] (Triaenophoridae) are proposed. Parabothriocephaloides Yamaguti, 1934, Penetrocephalus Rao, 1960 and Tetracampos Wedl, 1861 are resurrected as valid genera, whereas Alloptychobothrium Yamaguti, 1968 (newly synonymised with Plicatobothrium Cable & Michaelis, 1967), Capooria Malhotra, 1985 and Coelobothrium Dollfus, 1970 (syns of Bothriocephalus Rudolphi 1808), Fissurobothrium Roitman, 1965 (syn. of Bathybothrium Lühe, 1902), Paratelemerus Gulyaev, Korotaeva & Kurochkin, 1989 (syn. of Parabothriocephaloides Yamaguti, 1934) and Tetrapapillocephalus Protasova & Mordvinova, 1986 (syn. of Oncodiscus Yamaguti, 1934) are considered to be invalid. A recently erected genus, Dactylobothrium Srivastav, Khare & Jadhav, 2006, and its type- and only species, D. choprai Srivastav, Khare & Jadhav, 2006, are considered to be unrecognisable, because their descriptions contain a number of obvious errors and also indicate that a mixture of several taxa, probably of at least two cestode orders, were studied. Parabothriocephaloides wangi nom. nov. is proposed for Parabothriocephalus psenopsis Wang, Liu & Yang, 2004 from Psenopsis anomala in China in order to avoid a secondary homonymy. All 46 genera considered to be valid are revised, with their generic diagnoses amended on the basis of a critical examination of extensive museum and newly collected specimens. Despite apparent paraphyly or polyphyly of some bothriocephalidean families, especially the Triaenophoridae, the current classification restricted to four families, proposed by Bray et al. (1994), namely the Bothriocephalidae, Echinophallidae, Philobythiidae and Triaenophoridae, is provisionally retained with slight modifications until more molecular data on most genera are available. Keys to families and genera are provided.
Keywords: Cestoda; Male; Animals; Female; mužské pohlaví; ženské pohlaví; zvířata